Functional Genomics, Transcriptomics, and Proteomics Reveal Distinct Combat Strategies Between Lineages of Wood-Degrading Fungi With Redundant Wood Decay Mechanisms - Presley, Gerald N.; Zhang, Jiwei; Purvine, Samuel O.; Schilling, Jonathan S. (Frontiers in Microbiology, 2020)
Wood-degrading fungi vary in their strategies for deconstructing wood, and their competitive successes shape the rate and fate of carbon released from wood, Earth’s largest pool of aboveground terrestrial carbon. In this study, one-on-one interspecific interactions between two model brown rot (carbohydrate-selective) fungi, Gloeophyllum trabeum and Rhodonia (Postia) placenta, were studied on wood wafers where a clearly resolved interaction zone (IZ) could be generated, reproducibly. Comparative RNAseq and proteomics between the IZ and non-interacting hyphae of each species identified combative strategies for each fungus. Glycoside hydrolases were a relatively smaller portion of the interaction secretome compared to non-interacting hyphae. The interaction zone showed higher pectinase specific activity than all other sampling locations, and higher laminarinase specific activity (branched β-glucan proxy) was seen in the IZ secretome relative to equivalent hyphae in single-species cultures. Our efforts also identified two distinct competitive strategies in these two fungi with a shared nutritional mode (brown rot) but polyphyletic ancestral lineages. Gloeophyllum trabeum (Gloeophyllum clade) upregulated more secondary metabolite (SM) synthesis genes in response to a competitor than did R. placenta. R. placenta (Antrodia clade) upregulated a larger variety of uncharacterized oxidoreductases in interacting hyphae, suggesting that these may play a role in mediating competitor response in this fungus. Both species produced several hypothetical proteins exclusively in the interaction zone, leaving questions as to the function of these proteins. This work supports the existence of multiple interaction strategies among brown rot fungi and highlights the functional diversity among wood decay fungi.